In Vitro/Vivo Activity of Potential MCR-1 Inhibitor in Combination With Colistin Againsts mcr-1-Positive Klebsiella pneumonia - Zhou, Yonglin; Wang, Tingting; Guo, Yan; Liu, Shui; Wang, Jianfeng; Shen, Yingbo; Tang, Shusheng; Wang, Yang; Deng, Xuming (Frontiers in Microbiology, 2018)
Carbapenem resistance among strains of the nosocomial pathogen Klebsiella pneumoniae is increasing worldwide, causing serious clinical infections and higher mortality rates. Polymyxins are some of the few “last resort” options for treatment of carbapenem-resistant Enterobacteriaceae, including K. pneumoniae; however, the emergence of plasmid-mediated colistin resistance gene mcr-1 has largely rendered polymyxin-class antibiotics ineffective in a clinical setting. We previously identified a natural compound, pterostilbene, which has a synergistic effect in combination with polymyxins. Here, we aimed to determine whether pterostilbene application can restore the bactericidal activity of polymyxins against mcr-positive K. pneumoniae. Checkerboard MIC studies confirmed that pterostilbene reduces the MIC of colistin against mcr-1-positive human clinical K. pneumoniae isolates, with the bacteria going from resistant to sensitive, and also demonstrated a synergistic effect with colistin (FIC index = 0.11 ± 0.04 or 0.14 ± 0.04). Time-killing assays showed that individually, both pterostilbene and colistin failed to eradicate K. pneumoniae strains, while in combination, the two drugs effectively eliminated K. pneumoniae ZJ02 and K. pneumoniae ZJ05 by 1–3 h post-inoculation. And the CDT assay also showed increases in the zones of inhibition only for mcr-1-positive E. coli and K. pneumoniae isolates. A mouse infection model demonstrated that the survival rate of mice at 7 days post-intraperitoneal injection with a lethal dose of K. pneumoniae ZJ05 was significantly promoted from 0% to 67% following combination therapy. This is the first time a MCR-1 inhibitor has successfully been used in combination with colistin against human clinical MCR-producing K. pneumoniae isolates.